Digital Twin of Nature: Jurisdictional Challenges of Environmental Monitoring in Cyberspace - Baskoro, Aji (Alauddin Law Development Journal, 2025)
The development of digital twin technology enables the creation of virtual representations of ecosystems such as forests, oceans, and the atmosphere for environmental monitoring and disaster mitigation. However, the storage of ecological data on foreign servers raises critical issues of jurisdiction, ownership, and data sovereignty. This study aims to analyze the challenges of national jurisdiction in regulating ecological data ownership and protection, while assessing the role of cyber law as a legal instrument to reinforce state sovereignty over digital ecological assets. Employing a normative juridical method with statutory, conceptual, and comparative approaches, the research draws on primary legal sources, secondary literature, and international reports. The findings reveal a legal vacuum concerning ecological data protection, potential domination by foreign entities, and weak national regulatory capacity. Consequently, strengthening cyber law is essential to expand legal jurisdiction into cyberspace, safeguard eco-digital sovereignty, and promote international cooperation in protecting strategic environmental data.